An Attack on Quantum Circuits Based on the Error Rates of NISQ Systems and a Countermeasure - Acharya, Nikita; Saravanan, Vedika; Saeed, Samah Mohamed (Silicon Valley Cybersecurity Conference, 2021)
Noisy Intermediate Scale Quantum (NISQ) computers are subject to different sources of noise. To enhance the reliability of quantum computers, noise-aware quantum compilers are used to generate the quantum circuit. A quantum compiler maps the quantum circuit to a physical circuit that can be executed on the quantum hardware. A malicious compiler can launch several attacks to increase the error rates in the circuit, and thus, corrupt the circuit output. To detect these attacks, we utilize circuit test points, which provide the meta-information of the circuit errors, and thus, detect any unexpected changes in the circuit error rates.